Transforming Financial Reporting to Improve Accountability through Transparency in the Education Sector: Transformasi Pelaporan Keuangan untuk Meningkatkan Akuntabilitas melalui Transparansi di Bidang Pendidikan - Nava Dwi Utari; Wiwit Hariyanto (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the implementation of ISAK 35 in financial reporting at SDI Tarbiyatul Ummah, highlighting its significance for transparency and accountability in educational institutions. Through qualitative methods including interviews, observations, and documentation, it was found that the institution only relied on monthly cash book reports, failing to meet ISAK 35 standards. By reconstructing financial statements according to ISAK 35 guidelines, the study demonstrates the importance of adherence to accounting standards for improved transparency and accountability. This research contributes to filling the knowledge gap regarding financial reporting practices in educational institutions and provides recommendations for enhancing financial management practices in line with ISAK 35. Highlights: 1. ISAK 35 ensures transparency in financial reporting.2. Qualitative methods reveal institutional practices.3. Reconstruction enhances transparency and accountability in financial management. Keywords: Financial Reporting, ISAK 35, Educational Institutions, Transparency, Accountability